Earnings Premiums and Penalties for Self-Employment and Informal Employees around the World - Gindling, T. H.; Mossaad, Nadwa; Newhouse, David (World Bank, Washington, DC, 2016)
This paper examines the earnings premiums associated with different types of employment in 73 countries. Workers are divided into four categories: non-professional own-account workers, employers and own-account professionals, informal wage employees, and formal wage employees. Approximately half of the workers in low-income countries are non-professional own-account workers and the majority of the rest are informal employees. Fewer than 10 percent are formal employees, and only 2 percent of workers in low-income countries are employers or own-account professionals. As per capita gross domestic product increases, there are large net shifts from non-professional own-account work into formal wage employment. Across all regions and income levels, non-professional own-account workers and informal wage employees face an earnings penalty compared with formal wage employees. But in low-income countries this earnings penalty is small, and non-professional own-account workers earn a positive premium relative to all wage employees. Earnings penalties for non-professional own-account workers tend to increase with gross domestic product and are largest for female workers in high-income countries. Men earn greater premiums than women for being employers or own-account professionals. These results are consistent with compensating wage differentials and firm quasi-rents playing important roles in explaining cross-country variation in earnings penalties, and raise questions about the extent to which the unskilled self-employed are rationed out of formal wage work in low-income countries.